Ecclesiastical history and Nikephoros Kallistou Xanthopoulos (Wien)
184 sayfa
Keywords: “The Ecclesiastical History of Nicephorus Xanthopoulus, written at the turn of the 14th century in 18 books, presents a unique case of Byzantine historiography; it revives the literary genre of church history, having reached a climax in late antiquity, at a time when Byzantium, under Emperor Andronikos II. Palaiologos, was religiously redefining itself after the exile in Nicaea (1204–1261) as well as the traumatic Latin occupation and dissolved the enforced church union with the Pope. Against the background of political strengthening in consequence of the recapture of the capital and the denial of religious subordination Xanthopoulos wrote a new church history from the creation of the world until the year 610 n. Chr.; it is dedicated to the “new Constantine” Emperor Andronikos II., who has preserved Byzantium from the “heresy” of the Latins. The work extensively draws from the early Byzantine predecessors and, between criticism and admiration, aims at a revised compilation in the spirit of Byzantine mimesis and emulation. In order to analyze his work and sources by internationally recognized experts of each used author, a symposium was organized in 2011 whose results are presented in these proceedings“ --